Cost-Effectiveness of Conbercept vs. Ranibizumab for Age-Related Macular Degeneration, Diabetic Macular Edema, and Pathological Myopia: Population-Based Cohort Study and Markov Model - Cui, Zhuang; Zhou, Wei; Chang, Qinxue; Zhang, Tiantian; Wang, Hui; Meng, Xiangda; Liu, Yuanyuan; Yan, Hua (Frontiers in Medicine, 2021)
Background: With the advent of aging society of China, fundus diseases related to pathological neovascularization, including age-related macular degeneration (AMD), diabetic macular edema (DME), and pathological myopia (PM), have become an increasingly serious medical and health problems. As effective drugs of the treatment, conbercept and ranibizumab have been commonly used and covered by the national basic medical insurance in China. However, the pharmacoeconomic evaluation of conbercept vs. ranibizumab for DME and PM remains lacking. This study would assess the cost-effectiveness of conbercept and ranibizumab for the treatment of AMD, DME, and PM from the perspective of Chinese payers. Methods: A Markov chain model was constructed based on the visual conditions of the patient indicated by the number of letters in best corrected visual acuity (BCVA). We conducted models based on real-world scenario to calculate the cost per the quality-adjusted life-year (QALY) gained. A 1-year cycle length and a 10-year simulation treatment were applied and the number of injections of conbercept and ranibizumab was assumed to the average number within 10 years. Transition probabilities, costs, utility data, and other parameters were obtained from literature searches. A 3.5% discounting rate was applied for both the costs and utilities. Results: The incremental cost-effectiveness ratios (ICERs) were more favorable for conbercept than ranibizumab in treatment of AMD, DME, and PM, with associated ICER of 66,669 renminbi (RMB), −258,813 RMB, and −373,185 RMB per QALY gained. Compared with ranibizumab, the incremental effectiveness of conbercept in treatment of AMD, DME, and PM was −0.665 QALYs, 0.215 QALYs, and 0.029 QALYs, respectively. The sensitivity analysis showed the same findings, although the ICER is sensitive to the costs of this program. Conclusion: Under the current Chinese healthcare setting, conbercept is suitable and cost-effective in treatment of AMD, DME, and PM compared with ranibizumab.